2022
DOI: 10.1177/11782234221086728
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Quercetin Magnetite Nanoparticles and Targeted Radiotherapy in Treatment of Breast Cancer

Abstract: Quercetin is a potent cancer therapeutic agent present in fruits and vegetables. The pharmaceutical uses of quercetin are limited due to many problems associated with low solubility, bioavailability, permeability, and instability. In addition, the high doses of quercetin show toxic effects in clinical and experimental studies. Therefore, a new strategy is warranted to overcome these problems without the use of toxic doses. The iron oxide nanoparticles can be used as a drug delivery system. This study aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 75 publications
0
25
0
Order By: Relevance
“…One of the antidiabetic therapeutic approaches focuses on the inhibition of carbohydrate‐hydrolyzing enzymes such as α‐amylase and α‐glucosidase in the digestive system (Askar et al, 2022; El‐Shawi et al, 2023). The inhibitors of these enzymes evoke a marked reduction of the glucose absorption rate and consequently attenuate the postprandial hyperglycemia (Chiasson, 2006).…”
Section: Polysaccharides' Antidiabetic Action Mechanismsmentioning
confidence: 99%
“…One of the antidiabetic therapeutic approaches focuses on the inhibition of carbohydrate‐hydrolyzing enzymes such as α‐amylase and α‐glucosidase in the digestive system (Askar et al, 2022; El‐Shawi et al, 2023). The inhibitors of these enzymes evoke a marked reduction of the glucose absorption rate and consequently attenuate the postprandial hyperglycemia (Chiasson, 2006).…”
Section: Polysaccharides' Antidiabetic Action Mechanismsmentioning
confidence: 99%
“…Once the experiment was carried out three times, the average number of viable cells was determined. The percentage of viable cells and dilution were displayed on a graph [19,20]. The information was presented as a percentage of relative viability for vehicle control.…”
Section: In-vitro Cell Line Studymentioning
confidence: 99%
“…Our ancestors were totally dependent on a wide variety of plants to treat themselves from disease until the introduction of synthetic medicines. It is found that almost 2000 racial groups all over the world have their own unique medical understanding and experience. , This is because some vital components that possess antioxidant and anti-inflammatory properties are used in certain physiologic conditions . There were 90 drugs that are commercially available or approved worldwide in the period of 1982 to 2002, and 79% of them were from natural sources. Still a large portion of the population use medicinal plants as primary source to treat different diseases such as fever, pain, inflammation, diarrhea, and many other illnesses. , …”
Section: Introductionmentioning
confidence: 99%